Computerized Provider Order Entry Reduces Length of Stay in a Community Hospital - Schreiber, R.; Peters, K.; Shaha, S.H. (Applied Clinical Informatics, 2014)
Objective: Does computerized provider order entry (CPOE) improve clinical, cost, and efficiency outcomes as quantified in shortened hospital length of stay (LOS)? Most prior studies were done in university settings with home-grown electronic records, and are now 20 years old. This study asked whether CPOE exerts a downward force on LOS in the current era of HITECH incentives, using a vendor product in a community hospital.Methods: The methodology retrospectively evaluated correlation between CPOE and LOS on a per-patient, per-visit basis over 22 consecutive quarters, organized by discipline. All orders from all areas were eligible, except verbals, and medication orders in the emergency department which were not available via CPOE. These results were compared with quarterly case mix indices organized by discipline. Correlational and regression analyses were cross-checked to ensure validity of R-square coefficients, and data were smoothed for ease of display. Standard models were used to calculate the inflection point.Results: Gains in CPOE adoption occurred iteratively house-wide, and in each discipline. LOS decreased in a sigmoid shaped curve. The inflection point shows that once CPOE adoption approaches 60%, further lowering of LOS accelerates. Overall there was a 20.2% reduction in LOS correlated with adoption of CPOE. Case mix index increased during the study period showing that reductions in LOS occurred despite increased patient complexity and resource utilization.Conclusions: There was a 20.2% reduction in LOS correlated with rising adoption of CPOE. CPOE contributes to improved clinical, cost, and efficiency outcomes as quantified in reduced LOS, over and above other processes introduced to lower LOS. CPOE enabled a reduction in LOS despite an increase in the case mix index during the time frame of this study.Citation: Schreiber R, Peters K, Shaha SH. Computerized provider order entry reduces length of stay in a community hospital. Appl Clin Inf 2014; 5: 685–698http://dx.doi.org/10.4338/ACI-2014-04-RA-0029
Keywords: Computerized physician order entry system; CPOE; length of stay; meaningful use; HITECH Act